Prevalencia de microsporum canis en gatos asintomáticos y su importancia como zoonosis en la ciudad de Ambato - Llerena Ruiz, Kevin Ariel (2024)
Zoonoses are diseases that are naturally transmitted from vertebrate animals to humans and vice versa. Microsporum canis is a dermatophyte that is very well adapted to cats and in 90% of infected animals no lesions are visible. The objectives were: 1) To compare two methods of diagnosis of Microsporum canis, a dermatophyte culture medium (DTM Uranotest) versus the traditional Wood's lamp method in asymptomatic cats, 2) To relate the presence of Microsporum canis with the variables of weight, sex, age, breed, body condition, frequency of bathing and the product used when bathing. 3) To emphasize the importance of Microsporum canis as a zoonosis in the city of Ambato. This study was carried out in the nine urban parishes of the city of Ambato in 90 feline patients using the Wood's lamp method and subsequently taking a hair sample to place in a culture medium of dermatophytes DTM Uranotest. The statistical analysis allowed concluding that there are very significant statistical differences regarding the prevalence of the dermatophyte Microsporum canis, at the same time, demonstrating the non-significant association of the study variables with the prevalence of this dermatophyte. These results showed that the prevalence of Microsporum canis in asymptomatic cats in the city of Ambato has a low percentage of incidence.